The peopling of an african slave port: Annamaboe and the Atlantic world - Sparks, Randy J. (2021)
Annamaboe, located on the Gold Coast in modern-day Ghana,was a sleepy Fante fishing village when Dutch traders arrivedthere in 1638. The arrival of the Europeans ushered Annamaboeinto the Atlantic world and brought fundamental changes tothe town’s physical landscape, economic and cultural life, andliterally to its DNA as Europeans and Africans formed relationshipsthat gave rise to a substantial mixed-race population.Like other Atlantic towns and cities, Annamaboe grew as a conduitfor trade. Its traders funneled African trade goods —primarilyenslaved peoples but also gold, maize and other provisions— to Europe and the Americas and it brought in a varietyof products from Europe and around the world in exchange— fabrics, metals, manufactured goods, alcohol and tobacco— and distributed those goods into the interior. The Atlanticworld is defined by the movement of goods, ideas and peoplesaround it, and much of that movement operated through theurban hubs that grew up around the Atlantic. Much of the scholarshipon the Atlantic world has focused on the North Atlantic,particularly on the British Atlantic. This article’s focus onan African Atlantic port offers an important corrective to thatbias, a necessary one if we are to fully comprehend that world.